1993
DOI: 10.1152/jappl.1993.75.1.364
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of individual airways to methacholine in adult rat lung explants

Abstract: We used a modified adult lung explant technique to directly measure the area of individual airways before and after methacholine (MCh) administration. Lungs were removed from 12-wk-old male Lewis rats under sterile conditions, filled with an agarose-containing solution at 37 degrees C, and cooled to 4 degrees C. Transverse slices (0.5–1.0 mm thick) were cut and cultured overnight. Concentration-response curves to MCh were determined for explant airways from lungs inflated to 25, 50, 75, and 100% total lung cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 0 publications
2
95
1
Order By: Relevance
“…Another concern is that the high pulmonary pressures of up to 30 cmH 2 O, used for filling the lungs with agarose, may alter recoil and tethering forces as well as the parenchyma-airway interdependence. DANDURAND et al [27] investigated the effect of different agarose filling volumes on airway area and methacholine responsiveness in razor bladecut rat lung slices. They observed that increasing lung volume resulted in increased airway area, but had no effect on maximal airway narrowing (if comparing filling with 50 or 75-100% TLC, although a small effect between 25-100% TLC was reported) or the EC50.…”
Section: The Model Of Precision-cut Lung Slicesmentioning
confidence: 99%
“…Another concern is that the high pulmonary pressures of up to 30 cmH 2 O, used for filling the lungs with agarose, may alter recoil and tethering forces as well as the parenchyma-airway interdependence. DANDURAND et al [27] investigated the effect of different agarose filling volumes on airway area and methacholine responsiveness in razor bladecut rat lung slices. They observed that increasing lung volume resulted in increased airway area, but had no effect on maximal airway narrowing (if comparing filling with 50 or 75-100% TLC, although a small effect between 25-100% TLC was reported) or the EC50.…”
Section: The Model Of Precision-cut Lung Slicesmentioning
confidence: 99%
“…Lung explants were prepared according to a modification [14] of the method of DANDURAND et al [13] which is presented here in brief. Using sterile technique, the lungs were removed from the chest cavity, the heart dissected free, and a 14-gauge catheter inserted into the trachea.…”
Section: Explant Preparation and Exposurementioning
confidence: 99%
“…As DANDURAND et al [13] have previously shown that the degree of inter-animal variability in airway responsiveness is less than intra-animal variability, and it has been demonstrated that intra-animal variability depends largely on airway size [14], all of the explants in each group were pooled. Explants from smoke-exposed and control rats were then randomly divided into six groups; the explants in each of the tests were incubated in medium plus supplement, as indicated below, for 30 min.…”
Section: Explant Preparation and Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…DANDURAND et al [7] have recently demonstrated the principal applicability of lung slices to study airway constriction. With lung slices, constriction of airways can be observed directly under a microscope.…”
mentioning
confidence: 99%